The metronomic combination of paclitaxel with cholinergic agonists inhibits triple negative breast tumor progression. Participation of M2 receptor subtype - Español, Alejandro Javier (2020)
Triple negative tumors are more aggressive than other breast cancer subtypes and there is a lack of specific therapeutic targets on them. Since muscarinic receptors have been linked to tumor progression, we investigated the effect of metronomic therapy employing a traditional anti-cancer drug, paclitaxel plus muscarinic agonists at low doses on this type of tumor. We observed that MDA-MB231 tumor cells express muscarinic receptors, while they are absent in the non-tumorigenic MCF-10A cell line, which was used as control. The addition of carbachol or arecaidine propargyl ester, a non-selective or a selective subtype 2 muscarinic receptor agonist respectively, plus paclitaxel reduces cell viability involving a downregulation in the expression of ATP “binding cassette” G2 drug transporter and epidermal growth factor receptor. We also detected an inhibition of tumor cell migration and anti-angiogenic effects produced by those drug combinations in vitro and in vivo (in NUDE mice) respectively. Our findings provide substantial evidence about subtype 2 muscarinic receptors as therapeutic targets for the treatment of triple negative tumors.